Genetic Variability of Coffee (Coffea arabica L.) Germplasm in Biennial Bearing and Its Influence on Selection Efficiency - Dawit Merga; Lemi Beksisa; Wakuma Merga; Desalegn Alemayehu (International Journal of Agronomy)
Arabica coffee is a perennial cash crop and highly affected by biennial bearing which disturbs farmers’ annual income and world’s coffee industries. Developing nonbiennial bearing variety is prominent in addition to applying field management practices. This study was conducted from 2012 to 2020 in southwestern Ethiopia at Tepi and Gera to test the extent of genetic variability among Arabic coffee germplasm in biennial bearing and understand the influences of bienniality on advanced selection. The pooled analysis of variance revealed handiness of genetic variability in yield and biennial bearing. The moderate genotypic coefficient of variation (10–20%), heritability (30–50%), and high genetic advance as percentage of the mean (>20%) were manifested in yield and biennial bearing. Response to selection and selection efficiency were negatively affected by biennial bearing. Early selection excluded 30–40% of the top high yielders from advanced selection. Selection at four harvesting seasons revealed 90% and more selection efficiency. Thus, one has to be conscious of the alternate bearing nature of lines during advanced selection. Both T43/11 and T51/11 were among the top high yielders and showed low biennial bearing at Gera and Tepi. T33/11, T49/11, T55/11, and T61/11 showed very low biennial bearing at both locations. These are promising lines and could be recommended for further biennial bearing improvement breeding programs.